Decision Support System for Determining Academic Advisor Using Simple Additive Weighting - Sivaram M.; Shanmugapriya S.; Yuvaraj D.; Porkodi V.; Akbari A.; Hashim W.; Maseleno A.; Huda M. (Springer, 2023)
Artificial intelligence; Decision making; Decision support systems; Soft computing; Academic fields; Higher education; Simple additive weighting; Tertiary institutions; Students